2009
DOI: 10.1097/ccm.0b013e31819ceb71
|View full text |Cite
|
Sign up to set email alerts
|

Platelets support pulmonary recruitment of neutrophils in abdominal sepsis*

Abstract: These data demonstrate that platelets play a key role in regulating infiltration of neutrophils and edema formation in the lung via upregulation of Mac-1 in abdominal sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
121
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 134 publications
(132 citation statements)
references
References 48 publications
10
121
1
Order By: Relevance
“…However, results from that investigation are difficult to interpret because of inconsistencies in inflammatory responses and bacterial counts. For example, Meng et al (34) reported that pulmonary accumulation of neutrophils were lower 24 h compared with 6 h after CLP, which is in contrast to most studies on CLP-induced neutrophil recruitment (4,6,43). Moreover, in that study, it was reported that rhDNAse decreased bacterial counts in the blood but not in the peritoneal cavity, lung, or liver 24 h after CLP induction.…”
contrasting
confidence: 48%
“…However, results from that investigation are difficult to interpret because of inconsistencies in inflammatory responses and bacterial counts. For example, Meng et al (34) reported that pulmonary accumulation of neutrophils were lower 24 h compared with 6 h after CLP, which is in contrast to most studies on CLP-induced neutrophil recruitment (4,6,43). Moreover, in that study, it was reported that rhDNAse decreased bacterial counts in the blood but not in the peritoneal cavity, lung, or liver 24 h after CLP induction.…”
contrasting
confidence: 48%
“…In models of lung inflammation induced by acid or abdominal sepsis, platelet depletion prevents both inflammation and vascular leakage, [37][38][39] pointing to a potential role of platelets in vascular permeability during lung inflammation. However, it remains unclear whether leakage occurring in lungs is mediated directly by a platelet-derived mediator or via the overall enhancement of inflammation by platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, plateletneutrophil and platelet-endothelial cell interactions are suggested to participate to leakage of vasculature in lungs and brain. [37][38][39][50][51][52] In addition, the 13 different receptor subtypes for serotonin are capable of mediating distinct functions. 53 Thus, the cell combination present in the vasculature and a unique pattern of expression of the various serotonin receptors might conceivably result in prevention versus promotion of vascular permeability.…”
mentioning
confidence: 99%
“…Activated neutrophils release tissue destructive substances, such as reactive oxygen species and proteolytic enzymes, which, in turn, cause lung edema and impaired gaseous exchange (13,22). One study reported that platelets exert a key role in activating neutrophils in polymicrobial sepsis (2). This platelet-dependent activation of neutrophils appears to be mediated by CD40 ligand (CD40L) secreted from activated platelets (26).…”
mentioning
confidence: 99%